Leukemia derived dendritic cell (DCleu) mediated immune response goes along with reduced (leukemia-specific) regulatory T-cells - Pepeldjiyska, Elena; Li, Lin; Gao, Jincheng; Seidel, Corinna Lesley; Blasi, Christian; Özkaya, Erdem; Schmohl, Jörg; Kraemer, Doris; Schmid, Christoph; Rank, Andreas; Schmetzer, Helga Maria (Immunobiology, 2022)
The blastmodulatory Kit-M, composed of granulocyte-macrophage colony-stimulating-factor (GM-CSF) and Prostaglandin E1 (PGE1), is known to convert myeloid leukaemic blasts (from AML patients) into leukaemia derived dendritic cells (DCleu), which activate immunoreactive cells to gain antileukemic/leukaemia-specific activity. In this study we had a special focus on the influence of Kit-M treated, DC/DCleu containing patients'whole blood (WB, n = 16) on the provision of immunosuppressive regulatory T-cells. We could confirm that Kit-M significantly increased frequencies of (mature) dendritic cells (DC) and DCleu from leukemic whole blood (WB) without induction of blast proliferation. After mixed lymphocyte culture (MLC) with patients’ T-cells we confirmed that DCleu mediated leukemia-specific responses- going along with activated and leukemia-specific T- and NK-cells in an intracellular cytokine staining assay (ICS) and a degranulation assay (Deg)- resulted in an increased anti-leukemic cytotoxicity (Cytotoxicity Fluorolysis Assay = CTX). We could demonstrate that (leukemia-specific) CD4+ and CD8+ regulatory T-cell population (Treg) decreased significantly after MLC compared to controls. We found significant positive correlations of leukemia-specific CD3+CD4+ cells with frequencies of (mature) DCleu. Achieved anti-leukemic cytotoxicity correlated significantly positive with leukemia-specific CD3+CD8+ cells and significantly negatively with (leukemia-specific) Treg. In summary we demonstrate that immunesuppressive (leukemia-specific) regulatory T-cells are significantly downregulated after Kit-M triggered MLC- going along with a (reinstalled) antileukemic reactivity of the immune system (as demonstrated with functional assays ICS, Deg, CTX).
CRIS-Team Scopus Importer:2022-08-05
Keywords: Acute myeloid leukaemia; Anti-leukaemic functionality; Leukemia derived DC; Leukemia-specific cells; Regulatory T cells